Contemporary human resource management: Text and cases - Wilkinson, Adrian; Dundon, Tony; Yates, Edward (New Delhi Sage India, 2025)
Written by experts in the field, the seventh edition of this well-established book provides a critical and academically rigorous exploration of the key functions, practices and issues in HRM today. The first part of Contemporary Human Resource Management covers fundamental HRM practices while the second half examines contemporary themes and issues such as technology and climate change. The book contains over 50 thought-provoking case studies, showing you how theory relates to real-world examples.